Exploring Undergraduate Students’ Motivation-regulation Strategies in Thesis Writing - Diasti, Krismalita Sekar; Mbato, Concilianus Laos (Universitas Negeri Semarang, 2020)
Self-regulation is an ability that helps the students to maintain their effort in achieving their goals. In self-regulation, students can plan, monitor, and evaluate their learning process. Self-regulation encompasses many aspects. One of them is motivation. Motivation is considered as one of the important aspects of the learning process. Concerning the educational context in Indonesia, thesis writing course is a compulsory course. However, students are required to do the task independently. Therefore, students have to be self-regulated learners during the process of thesis writing. This study aims to investigate students’ motivation-regulation strategies in thesis writing. There were 9 participants involved in this study. The participants were students of English Language and Education Study Program of Sanata Dharma University. This study belongs to mixed-method research. Questionnaire and interview were used as instruments to collect the data. The results of this study revealed that the participants used some motivation-regulation strategies, namely, self-consequating, environmental structuring, goal-oriented self-talk, interest enhancement, and attribution control. Additionally, the majority of the participants were apt to procrastinate writing their thesis. The implications are provided for undergraduate students, thesis advisor, and future researchers.